A trajetória acadêmica e os desafios dos alunos indígenas no ensino superior no município de Humaitá – AM - Bernardo, Alberlândia de Lima (Brasil, 2021)
In the last few years there has been a significant increase in the enrollment of indigenous students in Brazilian public universities, this increase has been enhanced by the policy of affirmative actions, which have enabled the access of indigenous students to higher education. This work aims to analyze the academic trajectory and the challenges that indigenous students face when they leave their villages to attend an undergraduate course at a university. We start from the assumption that after centuries of contact and domination, these peoples decided to appropriate the scientific knowledge to solve the daily problems arising after contact. Our research seeks to understand these issues from the life stories of indigenous students enrolled in undergraduate courses at UFAM and UEA in the municipality of Humaitá - AM. The data showed, among other things, that the financial aspect is one of the biggest challenges in the journey of students who leave their villages to study in urban centers.